2021
DOI: 10.1002/pol.20210699
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the anion on electrochemically doped regioregular and regiorandom poly(3‐hexylthiophene)

Abstract: Chemical and electrochemical doping of π-conjugated polymers is an important aspect in determining the performance and enabling the operation of many organic electronic devices, from organic light emitting diodes and thermoelectrics to organic electrochemical transistors. In both chemical doping and electrochemical doping an ionized dopant or counterion is present along with the doped π-conjugated polymer. This dopant or counterion is not a benign spectator, rather, its presence can significantly impact the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…The same fluorescence behavior was found for decreasing KCl concentrations in the incubation solution (Figure 2e and Figure 2f). The trends found for TFPB − and BF 4 − indeed agree with previous findings because small ions, such as BF 4 − , are known to have a small influence on the crystallinity of poly(3‐alkylthiophenes), which will facilitate the generation of the fluorescence signal [41] …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The same fluorescence behavior was found for decreasing KCl concentrations in the incubation solution (Figure 2e and Figure 2f). The trends found for TFPB − and BF 4 − indeed agree with previous findings because small ions, such as BF 4 − , are known to have a small influence on the crystallinity of poly(3‐alkylthiophenes), which will facilitate the generation of the fluorescence signal [41] …”
Section: Resultssupporting
confidence: 90%
“…À indeed agree with previous findings because small ions, such as BF 4 À , are known to have a small influence on the crystallinity of poly(3-alkylthiophenes), which will facilitate the generation of the fluorescence signal. [41] To our understanding, a change in the lipophilic anion has two effects: i) different oxidation degrees of the POT core, i.e., from POT 0 to POT + , decreasing the original fluorescence of pristine POT NPs, and ii) different effect on the crystalline domains in the POT structure, which are responsible for an enhanced fluorescence signal by the restriction of intramolecular motion (RIM). An increase in the mobile amorphous fraction with non-radiative energy dissipation paths has been shown to occur.…”
Section: Resultsmentioning
confidence: 99%
“…The Coulomb interaction between the charge carrier and its counterion is poorly screened by the low dielectric medium of most polymers, which lowers the mobility of the carrier. Several studies have focused on identifying factors or properties that affect Coulomb interactions. , A survey of the literature, however, shows that salient conclusions from these studies conflict. ,, Some studies correlate increased counterion size to reduced Coulomb interactions, , while others find no such correlation and instead correlate increased molecular ordering ,, with reduced Coulomb interactions. Moreover, translating molecular designs of undoped polymers with high mobility to doped polymers with high conductivity has been difficult.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39] For example, Baustert, et al recently showed that large ions are excluded from the crystalline regions of regioregular-poly(3-hexylthiophene), RR-P3HT, thus resulting in a shift of approximately 250 mV in the oxidation potential relative to when a small anion is used in the electrolyte solution. [37] Additionally, in OECTs, which rely on electrochemical doping, the performance parameters are highly dependent on the electrolyte ions. [35,36,40] This dependence on electrolyte chemistry makes electrochemical measurements preferable to photoemission measurements when the intended use of the material is in an electrochemical device.…”
Section: Introductionmentioning
confidence: 99%
“…Such solvent and electrolyte dependence is documented throughout the literature. [36][37][38][39] For example, Baustert, et al recently showed that large ions are excluded from the crystalline regions of regioregular-poly(3-hexylthiophene), RR-P3HT, thus resulting in a shift of approximately 250 mV in the oxidation potential relative to when a small anion is used in the electrolyte solution. [37] Additionally, in OECTs, which rely on electrochemical doping, the performance parameters are highly dependent on the electrolyte ions.…”
Section: Introductionmentioning
confidence: 99%